Preparation and Characterization of Electrodes Modified with Pyrrole Surfactant, Multiwalled Carbon Nanotubes and Metallophthalocyanines for the Electrochemical Detection of Thiols - Zagal-Moya, J; Zagal-Moya, J (2014)
Sin Editorial Disponible